Amphipod Isotope Composition, Condition and Reproduction in Contrasting Sediments: A Reciprocal Transfer Experiment - Garrison, Julie A.; Karlson, Agnes M. L.; Nascimento, Francisco J. A. (Frontiers in Marine Science, 2022)
Eutrophication is a process that results in excessive phytoplankton blooms, which sink to the sediment and enrich the organic matter (OM). This alters the available resources to benthic organisms and may have consequences for feeding ecology and reproduction strategies of marine populations. While effects of eutrophication on biodiversity are well documented, the more subtle effects of OM on population dynamics and diet plasticity are understudied. We performed a reciprocal transfer experiment with the benthic bioindicator amphipod Monoporeia affinis from two stations in the Baltic Sea with differing sediment OM (low and high) creating four treatments (low control, low transferred, high transferred, and high control). We investigated sediment OM effects on: i) the dietary niche and organism body condition of two different life stages of M. affinis utilizing bulk stable isotopes δ13C and δ15N, and C:N ratio; and ii) M. affinis fecundity and embryo viability. There was no initial significant differences between the females from different stations in terms of δ13C, δ15N, C:N, fecundity or viable embryos. However, we found that moving females from high OM to low OM (where the low OM sediment has higher δ15N and lower δ13C) significantly depleted their 13C values, while amphipods in low OM sediment had always significantly enriched 15N regardless of female origin indicating feeding on the new sediment. Although end-of-experiment females had lower C:N than initial females, individuals in low OM sediment presented significantly higher C:N (indicating higher body condition) than those in high OM sediment. Conversely to adult amphipods, no effects of OM were seen for juveniles δ13C or δ15N, but their individual biomass was larger in high OM sediment treatments and high OM transferred to low OM sediment. Our results indicate that the low range of sediment OM tested here altered female amphipod δ13C, δ15N and C:N ratios, with those in low OM treatments having a better body condition, but those in high OM treatments had a greater reproductive success in terms of offspring biomass. Our findings suggest a tradeoff between female condition and reproduction and indicates that even relatively small levels of sediment organic enrichment will impact female condition.